PRIORITISING CRITERIA OF MAINTENANCE FOR GREEN ROOF IN HIGH-RISE RESIDENTIALS - Saharuddin, Shafikah; Khalil, Natasha; Abdullah Saleh, Alia (Journal of Surveying, Construction and Property, 2020)
Numerous problems arise due to the development growth of a country such as the destruction of natural environments and the deficit in green spaces. Thus, in order to overcome these issues, an alternative by implementing green building has been introduced. One of the sustainable approaches in a green building that can be implemented is the green roof. The utilization of a green rooftop over structures has gradually turned into a pattern in urban communities as it gives various advantages to the nation. The objective of the study is to analyse the criteria of maintenance and the rank of each criterion in approaching towards the establishment of best practice of the maintenance for the green roof, by concentrating on high-rise buildings for residential. The data were collected from respondents using the distributed questionnaires through email and via online survey. A total of 30 maintenance managers were drawn as the sample for the study by using purposive sampling technique, where 20 were returned and valid for analysis. Descriptive statistic of mean ranks and standard deviations was adopted for analysis. The most significant criteria in green roof maintenance are drainage, followed by waterproofing, irrigation, water retention and roof slab, based on the result obtained. The result of the study provides a significant improvement to the existing practice in the maintenance practice of the green roof by highlighting its maintenance criteria and key address, as it may assist to standardize the maintenance practice of green roofs in the Malaysian tropical climate.